Tolerance Stack Analysis in Francis Turbine Design - Indra Djodikusumo; Koko Suherman; Paskalis Bowo A. Oken (Journal of Engineering and Technological Sciences, 2010)
The  tolerance  stacking  problem  arises  in  the  context  of  assemblies from  interchangeable  parts  because  of  the  inability  to  produce  or  to  join  parts exactly  according  to  nominal  dimensions.  Either  the  relevant  part's  dimension varies around some nominal values  from part to part or the act of assembly that leads  to  variation.  For  example,  as  runner  of  Francis  turbine  is  joined  with turbine shaft via mechanical lock,  there is not only variation in the diameter of runner  and the concentricity between the runner  hole  and  turbine  shaft, but also the  variation in  concentricity  between  the  outer  parts  of  runner  to runner hole. Thus,  there  is  the  possibility  that  the  assembly  of  such  interacting  parts  won't function  or  won't  come  together  as  planned.   Research  in  this  area  has  been conducted and 2 mini hydro Francis turbines (800 kW and 910 kW) have been designed and manufactured for San Sarino and Sawi Dago 2 in Central Sulawesi. Experiences  in  analyzing  the  tolerance  stacks  have  been  documented.  In  this paper it will be demonstrated how the requirements of assembling performance are derived to be the  designed    tolerances  of each interacting component, such  a way that the assembling would be functioning and come together as planned.